Co2P-Induced Abnormal Electrolyte Decomposition Encountered with LiCoPO4. (1st January 2015) - Chen, Weibing; Fang, Haisheng; Yang, Bin; Ma, Wenhui
Abstract : Herein an abnormal increase of electrolyte decomposition is observed for LiCoPO4 and a new effect of Co2 P is revealed. Our study demonstrates that the presence of Co2 P even in a small amount can significantly accelerate the electrolyte decomposition at high voltage in the charge process for LiCoPO4 due to the catalytic property of Co2 P. Such a catalytic effect of Co2 P can account for the abnormal increase of electrolyte decomposition observed for bigger LiCoPO4 crystals. Therefore, the formation of Co2 P should be precluded in the synthesis of LiCoPO4, and such a requirement will have a drastic consequence on material processing.